Problem-solving cases in Microsoft Access and Excel - Brady, Joseph A.
Now in its Fourth Annual Edition, Problem-Solving Cases in Microsoft Access and Excel helps build spreadsheet and database skills using brand new realistic business cases and is the perfect complement to any computer literacy or MIS course. Each case introduces an interesting and realistic business problem and, with the help of tutorials on Microsoft Access and Excel, trains users in critical thinking and problem solving using application software. The new scenarios added to this edition reflect real business situations, ranging from small, privately-owned companies to large corporations